2020
DOI: 10.3389/fimmu.2020.529219
|View full text |Cite
|
Sign up to set email alerts
|

Th1-Dependent Cryptococcus-Associated Immune Reconstitution Inflammatory Syndrome Model With Brain Damage

Abstract: Cryptococcus -associated immune reconstitution inflammatory syndrome (C-IRIS) is identified upon immune reconstitution in immunocompromised patients, who have previously contracted an infection of Cryptococcus neoformans ( Cn ). C-IRIS can be lethal but how the immune system triggers life-threatening outcomes in patients is still poorly understood. Here, we establish a mouse model for C-IRIS with Cn serotype A strain H99, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 56 publications
4
44
0
Order By: Relevance
“…Once the immune suppression is relieved by effective antifungal treatment, aberrant immune responses and excessive CNS inflammation would same occur, and finally results in IRIS events in non-HIV patients. Our data showed that IL-12/IL-10 ratio that represented Th-1/Th-2 balance was significantly lower at baseline in the IRIS group, and increased inversely at IRIS occurrence, which is consistent with the study from Panackal et al,28 and indicated an immune reconstitution.Associations between high chemokine expressions and IRIS development were identified in HIV and non-HIV populations as previously reported 9,12,29. Elevated CSF IFNγ, IL-4, IL-10, IL-17, CXCL10, CCL3 and MCP-1 levels were recognised as biomarkers for IRIS in HIV population, whereas our data showed th1 cytokines (TNFα), th2 cytokines (IL-4, IL-10) and chemokines (MCP-1, MIP-1α, MIP-1β) all increased at baseline CSF, indicating that IRIS is a complicated immune response in both HIV and non-HIV populations.…”
supporting
confidence: 69%
“…Once the immune suppression is relieved by effective antifungal treatment, aberrant immune responses and excessive CNS inflammation would same occur, and finally results in IRIS events in non-HIV patients. Our data showed that IL-12/IL-10 ratio that represented Th-1/Th-2 balance was significantly lower at baseline in the IRIS group, and increased inversely at IRIS occurrence, which is consistent with the study from Panackal et al,28 and indicated an immune reconstitution.Associations between high chemokine expressions and IRIS development were identified in HIV and non-HIV populations as previously reported 9,12,29. Elevated CSF IFNγ, IL-4, IL-10, IL-17, CXCL10, CCL3 and MCP-1 levels were recognised as biomarkers for IRIS in HIV population, whereas our data showed th1 cytokines (TNFα), th2 cytokines (IL-4, IL-10) and chemokines (MCP-1, MIP-1α, MIP-1β) all increased at baseline CSF, indicating that IRIS is a complicated immune response in both HIV and non-HIV populations.…”
supporting
confidence: 69%
“…Khaw et al recently demonstrated Th1 mediated brain damage in IRIS by Cryptococcus neoformans in mice [122]. Curiously, this appears associated with an aquaporin critical for brain water flow regulation that depends on Th1 [122]. In another report, Meya et al…”
Section: Fungal and Parasitic Co-infectionsmentioning
confidence: 99%
“…Jarvis et al evaluated cytokine responses in HIV-associated cryptococcal meningitis finding that macrophage activation linked to Th1 and Th17 activation in CSF was associated with cryptococci clearance and survival at 2 weeks [ 121 ]. Khaw et al recently demonstrated Th1 mediated brain damage in IRIS by Cryptococcus neoformans in mice [ 122 ]. Curiously, this appears associated with an aquaporin critical for brain water flow regulation that depends on Th1 [ 122 ].…”
Section: Opportunistic Infection In Hiv and Its Impact On The Inflmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, noncompromised CM patients often develop severe neurological pathology that is steroid responsive ( 6 ). CD4 + T cells also orchestrate lethal immune pathology in animal models ( 12 , 13 , 15 ). However, CD4 + cells do not perform their immune functions on their own but require antigen-presenting cellular partners to become activated and to execute their effector functions in neuroinflammatory diseases ( 16 ).…”
Section: Introductionmentioning
confidence: 99%